Three intronic lncRNAs with monoallelic expression derived from the MEG8 gene in cattle. (7th December 2016) - Yang, W.; Li, D.; Wang, G.; Zhang, C.; Zhang, M.; Zhang, W.; Li, S.
Summary: The field of long noncoding RNA (lncRNA) research has been rapidly advancing in recent years. Antisense lncRNAs, intergenetic lncRNAs and enhancer lncRNAs can regulate genomic imprinting, which leads to parent‐origin‐specific monoalletic expression of genes. However, the function of intronic ncRNAs in genomic imprinting remains unclear. Previously, we obtained the cDNA sequence of cattle MEG8 gene, which is located in the DLK1–DIO3 imprinted clusters of cattle chromosome 21. In this study, we undertook a systematic search for transcripts mapping to the MEG8 intronic region and identified three novel lncRNAs, named MEG8 intronic RNA 1 ( MEG8‐IT1 ), MEG8 intronic RNA 2 ( MEG8‐IT2 ) and MEG8 intronic RNA 3 ( MEG8‐IT3 ) according to the GENCODE annotated bibliography. We characterized the expression pattern of these lncRNAs using RT‐PCR in adult cattle tissues, and they were expressed in all tested eight tissues, similar to the expression pattern of MEG8 . The allele‐specific expression of three novel lncRNAs was assessed using a polymorphism‐based sequencing approach. Three single nucleotide polymorphism sites were identified in these three lncRNAs. We found that the three lncRNAs showed monoallelic expression in the analyzed tissues, suggesting that they may be imprinted in cattle. These results expand the number of known monoallelically expressed lncRNAs from the DLK1–DIO3 domain and contribute to further investigation of lncRNA regulatory mechanisms and function.